2021
DOI: 10.3390/pharmaceutics13081143
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase Activity of Bromelain Immobilized at Gold Nanoparticle Interfaces for Therapeutic Applications

Abstract: Bromelain (Bro) is a multiprotein complex extracted from the pineapple plant Ananas comosus, composed of at least eight cysteine proteases. Bro has a wide range of applications in medicine and industry, where the stability of its active proteases is always a major concern. The present study describes the improvement of stability and gain of specific activity in the enzymatic content of Bro immobilized on gold nanoparticles (GNPs). GNPs were synthesized in situ using Bro as the reducing and stabilizing agents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Brito et al. ( 20 ) showed that stability and gain of specific activity of bromelain protein complexes can be improved by immobilizing bromelain on gold nanoparticles. By applying CD spectroscopy, the authors observed structural changes in proteins upon binding to nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Brito et al. ( 20 ) showed that stability and gain of specific activity of bromelain protein complexes can be improved by immobilizing bromelain on gold nanoparticles. By applying CD spectroscopy, the authors observed structural changes in proteins upon binding to nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a study on the collagenase activity found in bromelain was conducted; here, the enzyme was immobilized with the use of a gold nanoparticle interface, which resulted in improvements in the thermal stability and enzymatic activity of this biomaterial in therapeutic applications that rely on the anti-inflammatory, anticoagulant, antitumor, antimetastatic in vitro properties and in vivo immunogenicity properties [98].…”
Section: Enzymatic Productsmentioning
confidence: 99%
“…Finally, a study on the collagenase activity found in bromelain was conducted; here, the enzyme was immobilized with the use of a gold nanoparticle interface, which resulted in improvements in the thermal stability and enzymatic activity of this biomaterial in therapeutic applications that rely on the anti-inflammatory, anticoagulant, antitumor, antimetastatic in vitro properties and in vivo immunogenicity properties [97].…”
Section: Enzymatic Productsmentioning
confidence: 99%